What Is the Most Appropriate Comparator to Use in Assessing the Comparative Performance of Primary Total Knee Prostheses? A Registry-Based Study - Khashayar Ghadirinejad, PhD; Stephen Graves, MD; Richard de Steiger, MD; Nicole Pratt, PhD; Lucian B. Solomon, MD; Mark Taylor, PhD; Reza Hashemi, PhD (Arthroplasty Today, 2024)
Background: The Australian Orthopedic Association National Joint Replacement Registry has developed a standardized multi-stage approach to identify prostheses with a higher-than-anticipated rate of revision when comparing a prosthesis of interest to all other prostheses within the same broad class. However, the approach does not adequately differentiate between the conventional and complex design prostheses, and the comparator classes need to be re-evaluated. This study aimed to identify a more relevant comparator to better reflect conventional and complex surgical practices according to the stability design and also explore how the rate of revision estimated in the comparator groups affects the identification of “prosthesis outliers.” Methods: The cumulative percent revision (CPR) was calculated for 640,045 primary total knee replacements (TKRs) undertaken for Osteoarthritis from 1 January 2003 to 31 December 2019. At first, survivorship analyses were undertaken to calculate the rate of revision for primary TKR by stability design. A modified TKR comparator group was developed by excluding the “complex” group of prostheses with fully stabilized and hinged designs. The effectiveness of the modified comparator groups, including cruciate retaining and posterior stabilized designs, was evaluated based on the ability to detect additional prostheses by performing the Australian Orthopedic Association National Joint Replacement Registry standardized method for identifying prosthesis outliers. Results: The modified comparator to include only conventional designs had a 10-year CPR of 5.2% (5.1, 5.3). When the fully stabilized and hinged design groups were combined as a comparator group of complex devices to reflect devices used only for specific purposes in primary TKR, the CPR at 10 year was 10.3% (8.6, 12.0). Conclusions: The use of modified comparator groups led to identifying additional conventional prostheses but fewer complex designs as being at risk and has the potential to improve the early assessment of TKR prostheses.